Improving the Capacity of Village Apparatus in the Implementation of Village Government Administration Services in Kadur Village, North Rupat District, Bengkalis Regency (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service activity was motivated by the limited capacity of village officials in providing government administration services, particularly in managing correspondence, archiving documents, and implementing standard operating procedures for services. This condition has resulted in the suboptimal quality of public services at the village level. The objective of this activity was to improve the capacity and competence of village officials in providing village government administration services to be more effective, efficient, and accountable. The method used was a participatory approach through the stages of problem identification, joint planning, regulation socialization, technical training, service simulations, and implementation assistance. The subjects of the activity were officials from Kadur Village, North Rupat District, Bengkalis Regency. The results of the activity showed an increase in the officials' understanding and skills in administrative management, the development of a more standardized administrative document format, and a growing collective awareness of the importance of orderly administration as part of good governance. In addition, internal leadership initiatives emerged that encouraged sustainable change within the village government environment. Overall, this activity had a positive impact on improving the quality of village administration services and was the first step towards a more professional transformation of village governance.